Numerical simulations of shear-thinning Oldroyd-B fluids in curved pipes - Arada, Nadir (2012)
The aim of this paper is to present a numerical study of steady generalized Newtonian and generalized Oldroyd-B flows with shear-thinning viscosity in a curved pipe of circular cross section and arbitrary curvature ratio. The combined effects of inertia, viscoelasticity and viscosity are studied, and the quantitative and qualitative behavior of the secondary motions are analyzed with respect to the corresponding characteristic parameters.